2022
DOI: 10.3389/fendo.2022.913062
|View full text |Cite
|
Sign up to set email alerts
|

Large Versus Small Gastric Pouch for Roux-en-Y Gastric Bypass in Individuals With Type 2 Diabetes and a Body Mass Index < 35 kg/m2: Six-Year Outcomes

Abstract: BackgroundRoux-en-Y gastric bypass (RYGB) results in extraordinary weight loss and glycemic control outcomes for patients with obesity; however, the effect of gastric pouch size is still unclear, and the reported results are contradictory. Additionally, long-term data on type 2 diabetes (T2D) patients with low body mass index (BMI) are sparse. This study was to assess the effect of 6-year outcomes in Chinese patients with T2D and a BMI &lt; 35 kg/m2 who underwent RYGB with gastric pouches of different size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The degree of change in gastric emptying can vary depending on postsurgical anatomical factors, including dimensions of the pouch and the width of the gastrojejunal anastomosis. In fact, some data suggest a smaller, rapid emptying gastric pouch may lead to improved weight loss and food tolerance after RYGB [72,73]. One study used high-resolution manometry to demonstrate that the Roux limb exhibits regular migrating motility complexes, suggesting that the gastric pouch and the Roux limb behave as a common cavity during food ingestion [74].…”
Section: Gastric Motilitymentioning
confidence: 99%
“…The degree of change in gastric emptying can vary depending on postsurgical anatomical factors, including dimensions of the pouch and the width of the gastrojejunal anastomosis. In fact, some data suggest a smaller, rapid emptying gastric pouch may lead to improved weight loss and food tolerance after RYGB [72,73]. One study used high-resolution manometry to demonstrate that the Roux limb exhibits regular migrating motility complexes, suggesting that the gastric pouch and the Roux limb behave as a common cavity during food ingestion [74].…”
Section: Gastric Motilitymentioning
confidence: 99%
“…MU formation is influenced by the size of the gastric pouch, as larger pouches contain a greater parietal cell mass that produces acid, resulting in increased acidity levels and a higher likelihood of developing ulcers [ 29 , 30 ]. It has been suggested that inflammation-inducing conditions and prolonged irritation from foreign materials, such as the use of non-absorbable suture material, staples leading to staple line dehiscence, and tension on the anastomosis, can increase the risk of MU.…”
Section: Physiopathology and Predictorsmentioning
confidence: 99%
“…The Roux-en-Y gastric bypass (RYGB) constitutes one of the most common and effective bariatric procedures performed in the treatment of obesity (1,2). During a RYGB, the receptive stomach is downsized to a small pouch the size of an egg (10-35ml) (3). The remaining portion of the stomach is no longer receptive to food and anastomosed to a proximal portion of the small intestine, the biliopancreatic limb.…”
Section: Introductionmentioning
confidence: 99%